2023
DOI: 10.1590/s1677-5538.ibju.2023.9909
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal testicular vessel distribution in human fetuses - basis for Fowler-Stephens surgery

Abstract: Purpose: To analyze the histology and distribution of abdominal testicular vessels in human fetuses Patients and Methods: We studied 19 fetuses (34 testes) ranging in age from 12 to 19 weeks post-conception. The fetuses were evaluated regarding crown-rump length (CRL), total length (TL) and body weight immediately before dissection. Each testis was dissected and embedded in paraffin, from which 5 µm thick sections were obtained and stained with Masson's trichrome and An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Dr. Benzi and collegues from Brazil performed on page 749 ( 8 ) a interesting translational study about the Fowler-Stephens surgery and concluded that the upper portion of the abdominal testis in human fetuses had a higher concentration of vessels than the lower portion. These results suggest that manipulation of the lower end of the testis during Fowler-Stephens surgery should be avoided in order to preserve the collateral circulation.…”
mentioning
confidence: 99%
“…Dr. Benzi and collegues from Brazil performed on page 749 ( 8 ) a interesting translational study about the Fowler-Stephens surgery and concluded that the upper portion of the abdominal testis in human fetuses had a higher concentration of vessels than the lower portion. These results suggest that manipulation of the lower end of the testis during Fowler-Stephens surgery should be avoided in order to preserve the collateral circulation.…”
mentioning
confidence: 99%